حق الانتفاع العقاري وتطبيقاته في صناديق الاستثمار العقارية في الفقه الإسلامي : ماليزيا أنموذجا - Che Adenan bin Muhammad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study examines the origins of usufruct and its types with a focus on usufruct of real estate and its relationship with some applications of the rights to usufructs that have been codified in Islamic jurisprudence. It also addresses the sides of consensus and dissension between the old types of usufruct of real estate in Islamic Jurisprudence and new types of usufruct of real estates that have been applied in Malaysia. The study also highlights the topic of contemporary Islamic Real Estate Investment Trust (i-REIT) which is related to the application of Islamic usufruct to real estate with an emphasis on the origin of the investment fund, its types, the compounds that relate to “Real Estate Transactions” and juristic judgements on it. The researcher presents the Malaysian experience as an example of the application of Islamic usufruct of real estate and selects two pioneering examples. The first one is the i-REIT in the al-Aqar Healthcare REIT company, and the second is the i-REIT in the al-Hadharah Boustead REIT company. Through these models, the study underlines the application of these funds especially in terms of their products and the nature of the contracts signed between these two companies and their subscribers with assessment of their compatibility with the legitimate i-REIT. In order to achieve the purpose of the study, the researcher has employed an inductive method by collecting and evaluating the opinion of classical and contemporary Muslim jurists and presenting their judgment and their evidence on this matter. Apart from that, an analytical method is used to discuss and examine these scholars views and theories in order to recommend the most appropriate one. The research also uses the empirical method to examine the role and practice of the two companies concerned. This study reveals that the practice of usufruct in contemporary Islamic real estate has various types and forms. They have generated a new product that can be classified as a tool to invest in assets that is in line with the shariah (Shariah compliant based investments). The study concludes that the i-REIT is a legitimate alternative to the conventional investment fund business and the conventional real estate investment trust market in Malaysia and around the world.